YOU LOOK DISGUISTING: KRITIK ATAS CITRA KECANTIKAN TELAAH SEMIOTIKA JOHN FISKE TERHADAP REPRESENTASI FEMINISME MODERN - Eka Bella Ferlinda Furkan; Dedi Kurnia Syah Putra (SEMIOTIKA: Jurnal Komunikasi, 2015)
‘You Look Disguisting’ (2005) is a short film that contains criticisms of the image of beauty in a woman's face. Beauty is associated with such a full manipulation of makeup. Beautiful presentation is no longer located on the face itself, but rather shifted to manipulate symbols, brand of cosmetic products. The conditions of their assumptions about modern feminism, where gender equality is no longer a tool of struggle of feminism, but feminism is today synonymous with beauty, and other feminine traits. You look disguisting trying to break the tradition of the shift, the film wants to restore the image of beauty does not lie in makeup, but lies in naturalitity. The French sociologist June Hannan (2007: 22) argues that feminism as a social movement to build an understanding of equal rights, there is no gender distinction between ownership of women and men. Furthermore, Hannan agreed that feminism has shifted from the initial meaning, where the interpretation of feminism today is more on the concept of existentialism femaleness. Look elegant, beautiful, charming and simbolistic. This journal will parse a more detailed presentation related to the criticism of feminism beauty that featured in the film ‘You Look Disguisting’. The theory in this research is the construction of social reality on modern feminism. This writing method approach is qualitative research which refers to The Television Code Theory of Semiotics from John Fiske. Keywords: Short Film, Television Codes Theory, Modern Feminism, Criticism Beauty